Open Source System as Innovation in Organizations: A Managerial Perspective on Its Adoption - Jaafar, Noor Ismawati; Yahya, Sharifah Fazlinda Sheikh (UI Scholars Hub, 2014)
This study identifies the factors that have a direct effect on a manager's decision towards Open Source System (OSS) enterprise system adoption in Malaysia. Using the Technology-Organization-Environment (TOE) framework, the research is initiated by inviting the managers in Malaysian organizations who implemented OSS. A survey was conducted via online OSS social communities and by sending emails to shortlisted public. A total of 124 managers from 124 organizations responded to the survey and the results showed that four out of six factors were found significant in this study. In the technological context, ‘perceived relative advantage’, ‘perceived compatibility and trialability’ and ‘perceived complexity’ factors were found significant in the OSS adoption. In the organizational context, ‘management support, knowledge and expertise’ was identified as the adoption factor. Two factors in the environmental context that was not supported were the ‘technology skills and services’ and ‘platform long term viability’ although previous studies suggested otherwise.